A Model for ITSM Software Selection using Fuzzy TOPSIS Approach - Saeed Rouhani; Mohammad Ali Shahhosseini; Ahad Zare Ravasan; Elham Rahmanianfar (Journal of Information Technology Management)
Nowadays a growing number of implementing informationtechnology service management (ITSM) frameworks proves the trends toimprove the IT services and processes in organizations. In order toimplement an ITSM projects successfully in an organization, it isessential to select a suitable ITSM solution. Evaluation and selection ofthe ITSM software packages is complicated and time consuming decisionmaking process. Selection of inappropriate ITSM solution can turn out tobe costly and adversely affects IT processes and services of theorganization. This paper presents a model for dealing with such aproblem, which is based on fuzzy TOPSIS approach. The presented ITILbased model breaks down ITSM solutions selection criteria into twobroad categories namely functional (service strategy, service design,service transition, service operation, continual service improvement) andnon-functional requirements (quality, technical, vendor, implementation)including totally 46 selection criteria. Finally, a numerical example isgiven in an IT service provider company to demonstrate the application ofthe proposed model.